Pengaruh Kepuasan, Motivasi Dan Iklim Kerja Terhadap Efektivitas Kerja Guru SMA Swasta Di Kecamatan Air Putih Kabupaten Batu Bara - Monika Maryance Magdalena Tampubolon; Syaiful Bahri; Elfrianto Elfrianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of satisfaction, motivation, and work climate on the effectiveness of private high school teachers in the Air Putih sub-district, Batu Bara district, and was carried out from June 2022 to August 2022. The results show that there is an effect of satisfaction on teacher work effectiveness. The magnitude of the influence is shown by the coefficient of determination R2 (R square) = 26.4, which means that satisfaction affects the efficacy of teacher work by 26.4%. The remainder, 73.6, shows the regression equation Å¶ = 27,096 + .708X1, which means that an increase will follow every rise of one value of job satisfaction in the effectiveness value of 0.708. The results also show that there is an influence of motivation on work effectiveness. The influence is indicated by the coefficient of determination R2 (R square) = 95.9, which means that work motivation's effect on teacher work's effectiveness is 95.9%, and other factors determine the remaining 4.1%. The results of the regression equation Å¶ = 27,096 + 1,152X2, which means that an increase will follow everyone's increase in the value of work motivation in the teacher's work effectiveness value of 1,152. The influence of the work climate on the effectiveness of the work of teachers. The magnitude of the influence is indicated by the coefficient of determination R2 (R square) = 94.8, which means that the working climate influences effectiveness by 94.8%, and other factors determine the remaining 5.2%. The results of a simple regression analysis show the regression equation Å¶ =:27.096+1.025X3, which means that an increase will follow every rise in the work climate value in the effectiveness value of 1.578. In conclusion, there is an influence of satisfaction (X1), motivation (X2), and work climate (X3) together on the effectiveness of teacher work (Y). yyKeywords: Satisfaction, Motivation, Work Climate, Teacher Work Effectiveness